Comparative hydrodynamics of 10 Mediterranean lagoons by means of numerical modeling. Issue 4 (9th April 2014) - Umgiesser, Georg; Ferrarin, Christian; Cucco, Andrea; De Pascalis, Francesca; Bellafiore, Debora; Ghezzo, Michol; Bajo, Marco
Abstract A comparison study between 10 Mediterranean lagoons has been carried out by means of the 3‐D numerical model SHYFEM. The investigated basins are the Venice and Marano‐Grado lagoons in the Northern Adriatic Sea, the Lesina and Varano lagoons in the Southern Adriatic Sea, the Taranto basin in the Ionian Sea, the Cabras Lagoon in Sardinia, the Ganzirri and Faro lagoons in Sicily, the Mar Menor in Spain, and the Nador Lagoon in Morocco. This study has been focused on hydrodynamics in terms of exchange rates, transport time scale, and mixing. Water exchange depends mainly on the inlet shape and tidal range, but also on the wind regimes in the case of multi‐inlet lagoons. Water renewal time, which is mostly determined by the exchange rate, is a powerful concept that allows lagoons to be characterized with a time scale. In the case of the studied lagoons, the renewal time ranged from few days in the Marano‐Grado Lagoon up to 1 year in the case of the Mar Menor. The analysis of the renewal time frequency distribution allows identifying subbasins. The numerical study proved to be a useful tool for the intercomparison and classification of the lagoons. These environments range from a leaky type to a choked type of lagoons and give a representative picture of the lagoons situated around the Mediterranean basin. Mixing efficiency turns out to be a function of the morphological complexity, but also of the forcings acting on the system.